Effects of tea polyphenols-chitosan complex solution on changes of quality indicators under storage in Miichthys miiuy - NI Jiadan; PAN Shizhe; DAN Fan; JIANG Yihong (浙江大学学报. 农业与生命科学版, 2018)
Taken Miichthys miiuy as an experimental material, we investigated the effects of tea polyphenolschitosan complex solution on changes of main quality indicators (biogenic amine content, volatile base nitrogen content, total bacterial counts) of Miichthys miiuy under 25℃ and 4℃ storage condition. Tea polyphenols and chitosan were formulated into a complex solution by an orthogonal experiment, and the biogenic amine content was used as an evaluation index to screen out the optimum proportion for inhibiting biogenic amine production. After treatment of the optimum proportion of tea polyphenols-chitosan complex solution, the contents of biogenic amines and volatile base nitrogen, and the total bacterial counts of Miichthys miiuy stored at 25℃ and 4℃ were determined and analyzed. The results showed that the complex solution of 3 g/L tea polyphenols and 10 g/L chitosan was the optimal proportion, which significantly reduced the content of biogenic amines in Miichthys miiuy under the storage of 25℃ for 24 h and 4℃ for 12 d, respectively. Moreover, the contents of biogenic amines and volatile base nitrogen, and total colonies in Miichthys miiuy stored at 25℃ and 4℃ were lower than those of the untreated control group, and their shelf life could be extended to 30-36 h and 12-15 d, respectively.